THE EARLIEST CHRISTIAN WAR: Second- and Third-Century Martyrdom and the Creation of Cosmic Warriors - Koscheski, Jonathan (Journal of religious ethics, 2011)
Many Christian historians and theologians hold the opinion that the early church condemned wholesale an active involvement in bloodshed. However, in light of evidence drawn from early Christian texts, most notably literature dealing with martyrdom, one finds that stance overly simplified. In fact, forms of early Christianity not only glorified war and violence in certain contexts but actively sought it out. This article enters into this conversation by applying a theory championed by Mark Juergensmeyer's Terror in the Mind of God. While this theory deals with modern examples of religious cultures of violence, his “stages of symbolic empowerment” apply surprisingly well to certain communities within the early orthodox church. The cosmic war complex that leads to nefarious figures such as the fanatic suicide bomber can be seen at work within the nascent matrix of the Church, which produced victims and warriors in the form of the voluntary martyrs.